Reporting HIV in Papua New Guinea: Trends and omissions from 2000 to 2010 - Cullen, Trevor and Callaghan, Ruth (Pacific Journalism Review : Te Koakoa, 2010)
This article presents the findings from a longitudinal content analysis on the reporting of HIV (Human Immunodeficiency Virus) in Papua New Guinea’s two national newspapers—The National and Post-Courier—in 2000, 2005 and 2010. The authors tried to answer two key questions: Did press coverage of the disease increase and did the topics change or remain the same? Data from the content analysis showed that coverage of the disease increased significantly during the ten-year study period, and that the framing of the disease moved beyond representing HIV as purely a health story to one that was linked to socio-economic conditions and cultural practices. The feature stories gradually showed more sensitivity to people living with HIV, while they recognised and challenged the social stigma still associated with the disease in much of the country.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYxNmkyLjEwNDA